Coercion in mental healthcare: time for a change in direction - Andrew Molodynski; Yasser Khazaal; Felicity Callard (BJPsych International, 2016)
Coercion has always been integral to the care and treatment of people who are mentally ill and there is no ‘perfect’ model in which coercion is absent. A number of interventions have shown promise in reducing the use of coercion, however, and we believe the evidence points to ways forward that may improve both the experience and the outcome of care.